Spray-Dried Plasma Promotes Broiler Chick Growth by Enhancing Immune Surveillance - Candice E. C. Blue; Yasin Jababu; Salam A. Ibrahim; Radiah C. Minor; Leonard L. Williams; Adedeji O. Adetunji; Rizwana Ali; Lea S. Young; Yewande O. Fasina (Animals, 2023)
Spray-dried plasma (SDP) contain a variety of functional proteins that play an immunomodulatory role. To evaluate the potential of SDP to stimulate the immune system, day-old Ross 708 male broiler chicks (200) were allocated randomly to five dietary treatments. Treatment 1 (CX) comprised chicks fed basal unmedicated corn–soybean meal (SBM) without the addition of SDP. Treatment 2 (MX) includes chicks fed unmedicated corn–SBM basal containing Bacitracin methylene disalicylate (BMD) at 0.055 g/kg diet. Treatments 3 (SDP1), 4 (SDP2), and 5 (SDP3) contained chicks given unmedicated corn–SBM basal, into which SDP was included at 10, 20, and 30 g/kg diet, respectively. On d 7, 14, and 21, chicks’ body weight and FCR were calculated. Additionally, leucocyte counts, oxidative status, and IgY concentrations were determined in blood. On d 23, fecal populations of selected indicator bacteria species were determined. Results showed that FCR for SP3 was superior (p < 0.05) to other treatments. Likewise, heterophil numbers decreased in MX and SDP treatments compared to CX. Circulating IgY concentration was higher for SDP dietary treatments (p < 0.05) compared to MX. In conclusion, dietary SDP at 30 g/kg enhanced immune surveillance by increasing circulating IgY levels, maintaining a normal oxidative state, and increasing gut Bifidobacteria, thereby improving chick growth performance.